STD knowledge amongst the 10th military unit police officers of the state of rio de janeiro - Varella, Renata Q.; Passos, Mariana D.L.; Goulart Filho, Rubem A. (Brazilian Journal of Sexually Transmitted Diseases, 2012)
Introduction: STD are a serious public health problem, causing various complications, such as infertility, cervical cancer, penile cancer, and various psychosocial problems. Objective: evaluate the knowledge of STD and risk factors of the acquisition of STD among the 10th Military Unit police officers of Rio de Janeiro State. Methods: cross-sectional epidemiological study through the distribution of individual and anonymous questionnaires. Target population: Military police officers from the 10th MU, located in Barra do Piraí, Rio de Janeiro State. The questionnaire consisted of 24 questions addressing social-demographic data (age, sex, marital status, military rank) and sexual behavior/risk practices (partnership type, sexual practices, condom use, number of partners, frequency of intercourse, alcohol use, illicit drugs). Results: 600 questionnaires distributed for a total of 771 military officers on active duty, 313 were answered, and 291 included for analysis. The average age was 36.9 years, 76.64% married, 89.7% aware of STD, 94.5% know how to prevent from STD, 90.37% had lessons about STD, 13.05% already had STD, 95.88% use contraceptives, 22.68% had more than 41 sexual partners during their lifetime, 40% had more than two sexual partners last year, 14.42% had six sexual partners in the last 12 months, 23% have an affair, about 13% reported intercourse with sex professionals, 9.27% reported group intercourse, 6.19% use alcohol during intercourse, 4% reported homossexual activity, 45.36% make sex twice to three times a week, 71.14% make oral sex, and 34.02% reported anal sex. Conclusion: the 10th MU police officers have high knowledge about STD and there is a considerable risk of acquiring STD by these individuals, since many of them do not use condoms, have multiple sexual partners and extramarital sex as well, make group intercourse and also with sex professionals.